The ubiquitin ligase RNF5 determines acute myeloid leukemia growth and susceptibility to histone deacetylase inhibitors - Khateb, Ali; Deshpande, Anagha; Feng, Yongmei; Finlay, Darren; Lee, Joo Sang; Lazar, Ikrame; Fabre, Bertrand; Li, Yan; Fujita, Yu; Zhang, Tongwu; Yin, Jun; Pass, Ian; et al. (Nature communications, 2021)
Acute myeloid leukemia (AML) remains incurable, largely due to its resistance to conventional treatments. Here, we find that increased abundance of the ubiquitin ligase RNF5 contributes to AML development and survival. High RNF5 expression in AML patient specimens correlates with poor prognosis. RNF5 inhibition decreases AML cell growth in culture, in patient-derived xenograft (PDX) samples and in vivo, and delays development of MLL-AF9–driven leukemogenesis in mice, prolonging their survival. RNF5 inhibition causes transcriptional changes that overlap with those seen upon histone deacetylase (HDAC)1 inhibition. RNF5 induces the formation of K29 ubiquitin chains on the histone-binding protein RBBP4, promoting its recruitment to and subsequent epigenetic regulation of genes involved in AML maintenance. Correspondingly, RNF5 or RBBP4 knockdown enhances AML cell sensitivity to HDAC inhibitors. Notably, low expression of both RNF5 and HDAC coincides with a favorable prognosis. Our studies identify an ERAD-independent role for RNF5, demonstrating that its control of RBBP4 constitutes an epigenetic pathway that drives AML, and highlight RNF5/RBBP4 as markers useful to stratify patients for treatment with HDAC inhibitors. Epigenetic changes are implicated in Acute myeloid leukemia (AML) tumorigenesis. Here, the authors show that the ubiquitin ligase RNF5 and its substrate RBBP4 contribute to AML development by regulating epigenetic-controlled transcription which determines AML sensitivity to HDAC inhibitors.